Penelusuran Islam Wetu Telu di Lombok Timur - Rr. Sri Setyawati Mulyaningsih; Bambang Eka Saputra; Lalu Mas’Ud (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the background, development, and existence of WetuTelu Islam in Bengkaung Hamlet, Danger Village, Masbagik District, East Lombok Regency. The research method using historical research is based on four activity steps: heuristics, criticism, interpretation, and historiography. The data sources used are written, spoken and artifact data sources. The results of the study show that the background to the emergence of Wetu Telu Islam is the existence of traditional social life which is still reflected in the Wetu Telu Islamic community in the region, where it is quite difficult to accept new things with modern identities even though this community is already under pressure and almost marginalized. The development of WetuTelu Islam in the region is only 2% which still survives, because many others have been enlightened to Islam which is Kaffah. The existence of WetuTelu Islam in modern times has begun to erode because many da'wah studies have been carried out by religious leaders, Kyai and Tuan Guru who teach Islam according to the guidance of the Al-Qur'an and Hadith. The conclusion of this paper is that the emergence of WetuTelu Islam was motivated by a tradition that is still strong. The development of WetuTelu Islam is almost extinct, and the existence of Islam has begun to have a few adherents. Keywords: Islam, Wetu Telu